EFEKTIVITAS COGNITIVE BEHAVIORAL THERAPY (CBT) DALAM MENGURANGI PERILAKU BULLYING - Millatul Hoiroh; Ade Irma Noviyanti; Dewi Masyitoh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to examine the effectiveness of Cognitive Behavioral Therapy (CBT) group counseling in reducing bullying behavior among students at MTs Darul Ulum As-Surur. Bullying remains a persistent problem in Indonesian schools, including religious-based institutions such as madrasah, despite their emphasis on moral education. This study used a quantitative approach with a quasi-experimental nonequivalent control group design, involving 20 eighth-grade students divided into an experimental group (n=10) that received six sessions of CBT-based group counseling and a control group (n=10) that received regular guidance and counseling services. Data were collected using a 24-item bullying behavior questionnaire covering four dimensions: physical, verbal, relational/social, and cyberbullying, which was proven valid (r-count > r-table = 0.422) and reliable (Cronbach's Alpha = 0.792). Data were analyzed using Paired Sample and Independent Sample t-Tests with the help of IBM SPSS Statistics 26. Results showed a significant decrease in bullying scores in the experimental group (pretest M=81.60 to posttest M=40.60; t=22.532; Sig.=0.002<0.05), while the control group showed no significant change (M=79.10 to M=76.80; t=3.214; Sig.=0.111>0.05). The Independent Sample t-Test confirmed a significant difference between the two groups' posttest scores (t=-20.307; df=18; Sig.=0.002<0.05; mean difference=-36.20). These findings indicate that CBT-based group counseling is effective in reducing bullying behavior among madrasah students and may serve as an evidence-based intervention model for school counselors.